Challenges and Solutions of Electronic learning among EFL Students at Sebha University (Journal of Human Sciences, 2024)
This study aims to investigate the obstacles and challenges that have been encountered by EFL students at Sebha University when implemented to electronic learning system, as well as to find out the suitable solutions for these problems. The participants of the study were 50 students; 38 females and 12 males who were enrolled in the semesters from the 4th till the 8th semester. Simi-structured interviews were utilized to collect data; the thematic approach was used for analyzing data and the qualitative descriptive method was employed in this study. The research study concludes that EFL students have faced some technical obstacles when integrated to online learning during the time of COVID 19 pandemic, i.e., ignorance of technology, unstable network and lack of smart phones and computers. Moreover, EFL students have faced some academic challenges with online learning, i.e., lack of teacher interaction, difficulties of self-reliance learning and lack of collaborative learning approach. As a result, some solutions are suggested by EFL learners to fix up the previous problems which are presented in replacing e-learning system to blended learning as well as providing the university support for encountering the technical problems. Finally, recommendations for teachers to implement the collaborative approach and enhancing the autonomous learning techniques are mentioned in this study.